2021
DOI: 10.5620/eaht.2021022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential eye or skin irritation/corrosion in rabbit exposed to TiO2 photocatalyst (GST)

Abstract: TiO2 NPs photocatalyst is widely used in a variety of applications and products in the environmental and energy fields, including self-cleaning surfaces, air and water purification systems, sterilization, hydrogen evolution, and photoelectrochemical conversion. The possible biological and safety effects of TiO2 dermal exposure and absorption have not been well studied and more investigations on the potential health hazards of the TiO2 are needed. This study aimed to investigate potential effect of local lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…TiO2 material, which is covered in this paper, the new TiO2 material, GST (100% anatase) prepared from the precipitated sludge using TiCl4 used as a coagulant to remove total phosphorus in the wastewater was manufactured to have cost-competitive lower than price of commercial material (P-25, Evonik Corp., a flame-made multiphasic TiO2 nanoparticles containing anatase and rutile) with excellent photocatalytic function [8,9]. We have been studied toxicological test as acute oral / dermal toxicity (TG 402, 423) in female rats by Seol et al [10], eye or skin irritation/corrosion in rabbit (TG 404, 405) by Kim et al [11] and 90-day oral repeated toxicity in rats by Kim et al Through these studies, we confirmed that http://eaht.org GST have no treatment-related effect for oral acute / repeated exposure (90-day, subchronic) or acute dermal and eye or skin. But the study for toxicological information on dermal repeated study (90-day, subchronic) has been not conducted.…”
Section: Introductionmentioning
confidence: 99%
“…TiO2 material, which is covered in this paper, the new TiO2 material, GST (100% anatase) prepared from the precipitated sludge using TiCl4 used as a coagulant to remove total phosphorus in the wastewater was manufactured to have cost-competitive lower than price of commercial material (P-25, Evonik Corp., a flame-made multiphasic TiO2 nanoparticles containing anatase and rutile) with excellent photocatalytic function [8,9]. We have been studied toxicological test as acute oral / dermal toxicity (TG 402, 423) in female rats by Seol et al [10], eye or skin irritation/corrosion in rabbit (TG 404, 405) by Kim et al [11] and 90-day oral repeated toxicity in rats by Kim et al Through these studies, we confirmed that http://eaht.org GST have no treatment-related effect for oral acute / repeated exposure (90-day, subchronic) or acute dermal and eye or skin. But the study for toxicological information on dermal repeated study (90-day, subchronic) has been not conducted.…”
Section: Introductionmentioning
confidence: 99%
“…New TiO 2 material used in this article, GST (Green Sludge Titanium, 100% anatase) prepared from the precipitated sludge using TiCl 4 used as a coagulant to remove total phosphorus in the wastewater was manufactured to have cost-competitive lower than price of commercial material (P-25, Evonik Corp., a flame-made multiphasic TiO 2 nanoparticles containing anatase and rutile) with excellent photocatalytic function [ 22 , 23 ]. In previous research using GST, we have been studied toxicological test as acute oral / dermal toxicity (TG 402, 423) in female rats by Seol et al [ 24 ], eye or skin irritation/corrosion in rabbit (TG 404, 405) by Kim et al [ 25 ] and 90-day oral repeated toxicity in rats by Kim et al [ 25 ]. Through these studies, we confirmed that GST have no treatment-related effect for oral acute / repeated exposure or acute dermal and eye or skin.…”
Section: Introductionmentioning
confidence: 99%